2012
DOI: 10.3390/ijms13077902
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Oligodeoxynucleotide Promotes the Differentiation of Osteoblasts via ERK and p38 MAPK Pathways

Abstract: A specific oligodeoxynucleotide (ODN), ODN MT01, was found to have positive effects on the proliferation and activation of the osteoblast-like cell line MG 63. In this study, the detailed signaling pathways in which ODN MT01 promoted the differentiation of osteoblasts were systematically examined. ODN MT01 enhanced the expression of osteogenic marker genes, such as osteocalcin and type I collagen. Furthermore, ODN MT01 activated Runx2 phosphorylation via ERK1/2 mitogen-activated protein kinase (MAPK) and p38 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…3 In our previous studies, an oligodeoxynucleotide (ODN) that was designed based on human mitochondrial DNA (MT01), was demonstrated to promote the proliferation and activation of osteoblasts and stimulate the proliferation and differentiation of bone marrow mesenchymal stem cells (BMSCs) into osteoblasts. [4][5][6][7] However, crucial problems such as poor oligonucleotide stability in the presence of nuclease activity in vitro and in vivo, and low intracellular penetration, would limit its wide application to enhance osteogenic capacity. 8 To overcome these problems, chemical modications of ODNs have been employed, mainly focusing on the phosphodiester backbone and/or the sugar moiety.…”
Section: Introductionmentioning
confidence: 99%
“…3 In our previous studies, an oligodeoxynucleotide (ODN) that was designed based on human mitochondrial DNA (MT01), was demonstrated to promote the proliferation and activation of osteoblasts and stimulate the proliferation and differentiation of bone marrow mesenchymal stem cells (BMSCs) into osteoblasts. [4][5][6][7] However, crucial problems such as poor oligonucleotide stability in the presence of nuclease activity in vitro and in vivo, and low intracellular penetration, would limit its wide application to enhance osteogenic capacity. 8 To overcome these problems, chemical modications of ODNs have been employed, mainly focusing on the phosphodiester backbone and/or the sugar moiety.…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells can differentiate into mature and functional osteoblasts that produce extracellular matrix proteins and proteins that regulate matrix mineralization (10). Runx2, also known as Cbfa1/AmI3, is a runt domain family protein, which acts as an osteoblast-specific transactivator essential for osteoblast differentiation and bone formation (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells can differentiate into mature and functional osteoblasts that produce extracellular matrix proteins and proteins that regulate matrix mineralization (10). Runx2, also known as Cbfa1/AmI3, is a runt domain family protein, which acts as an osteoblast-specific transactivator essential for osteoblast differentiation and bone formation (10)(11)(12)(13)(14). Zhang et al (11) showed that commitment of undifferentiated mesenchymal stem cells to an osteoprogenitor lineage was associated with the expression of Runx2, and Runx2 protein levels were significantly upregulated in quiescence (G 0 ) or during proliferative arrest induced by serum deprivation or by contact inhibition of osteoblast cells (15).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations